2014
DOI: 10.1002/jaal.302
|View full text |Cite
|
Sign up to set email alerts
|

Using Disciplinary Literacies to Enhance Adolescents' Engineering Design Activity

Abstract: This comparative case study describes the literacy practices of two groups of adolescents as they sought to solve authentic problems through engineering design processes. Three types of data were collected as the groups addressed these problems: video-and audio-recordings of their conversations; adolescent-generated products; and pre-and post-challenge interviews. The authors used existing coding schemes of engineering design activity to identify when the adolescents enacted different stages of engineering des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
2
16
0
Order By: Relevance
“…For instance, Loveland (2014) asserted that the application of comprehension strategies can support students' comprehension of relevant information in textbooks. Similarly, our previous work (Wilson, Smith, & Householder, 2014) indicated that high school students who applied comprehension strategies while reading their clients' problem statements understood the scope of the problem more fully than students who did not apply comprehension strategies while reading their clients' problem statements.…”
Section: Comprehension Strategies and Engineering Designsupporting
confidence: 58%
See 1 more Smart Citation
“…For instance, Loveland (2014) asserted that the application of comprehension strategies can support students' comprehension of relevant information in textbooks. Similarly, our previous work (Wilson, Smith, & Householder, 2014) indicated that high school students who applied comprehension strategies while reading their clients' problem statements understood the scope of the problem more fully than students who did not apply comprehension strategies while reading their clients' problem statements.…”
Section: Comprehension Strategies and Engineering Designsupporting
confidence: 58%
“…Authors of practitioner-oriented articles (Lacivita, 2006;Loveland, 2014;Wilson-Lopez & Gregory, 2015a) strategies can support students' comprehension of relevant information in textbooks. Similarly, our previous work (Wilson, Smith, & Householder, 2014) indicated that high school students who applied comprehension strategies while reading their clients' problem statements understood the scope of the problem more fully than students who did not apply comprehension strategies while reading their clients' problem statements. Collectively, these articles suggest CSI can support students' understandings of clients' problems and their understandings of relevant scientific information needed to solve those problems.…”
supporting
confidence: 58%
“…In this article, the authors—Amy, who specializes in literacy, and Stacie, who is a professional engineer—offer suggestions for incorporating engineering and literacy instruction with upper elementary students. These suggestions are based in previous research literature (Wilson, Smith, & Householder, ), in national science standards (NGSS Lead States, ), and in our experiences with co‐teaching monthly literacy‐infused engineering units in third‐ and fifth‐grade classrooms.…”
Section: Grades 3–5 Ngss and Associated Literacy Instructionmentioning
confidence: 99%
“…In sum, practicing comprehension strategies with carefully selected texts is one way to help students engage in engineering design processes (cf. Wilson et al, ). Summarizing the text can help students to review and define the problem; asking questions can help students to clarify aspects of the problem that are still confusing; predicting can help students generate ideas in relation to the problem; and inferring can help students to evaluate solutions or to identify constraints inherent in the situation, which are oftentimes left implicit (Dym & Little, ).…”
Section: Comprehension Strategy Instruction and Engineering Design Prmentioning
confidence: 99%
“…Recognizing that language and literacy are central to the sociocultural practice of engineering, we draw upon work in disciplinary literacies (Wilson, Smith, & Householder, 2014) and engineering design thinking (e.g., Crismond & Adams, 2012) to identify the various ways that educators might help their students represent and communicate meaning during engineering learning experiences.…”
Section: Theoretical Perspectivementioning
confidence: 99%